Implementasi Rancang Bangun Alat Penetas Telur Lalat Black Soldier Fly dengan Metode Rasional - Putriliani, Nadia; Fithriyana, Inna; Talitha, Tita (Universitas Suryakancana, 2024)
UMKM Rekayasa Produk Organik (REPRO) Maggot located in Dusun Nongko Lanang, Wonolopo, Mijen District, Semarang City is a start-up business that takes advantage of opportunities in maggot cultivation that has been established for approximately one year. In the maggot cultivation process, there is a hatching process for Black Soldier Fly (BSF) eggs which requires a temperature of 28oC-36oC and a humidity of 60%-80%. If the temperature and humidity are unstable, it can affect the length of the egg hatching process. The BSF fly egg hatching process takes 3 days. However, in UMKM REPRO Maggot, the BSF egg hatching process takes 7-8 days. Therefore, a design for a Black Soldier Fly (BSF) egg incubator is needed which is equipped with temperature and humidity control to increase the level of effectiveness and efficiency. This design uses a rational method approach that contains several stages including: 1) clarifying objectives, (2) establishing function, (3) setting requirements, (4) determining characteristics, (5) generating alternatives, (6) evaluating alternatives, and (7) product improvements. The results of the trials that have been carried out obtained an increase in output efficiency of 86% and time effectiveness of 100% in the first trial, while in the second trial, 90% efficiency and 33.33% effectiveness were obtained. UMKM Rekayasa Produk Organik (REPRO) Maggot yang terletak di Dusun Nongko Lanang, Wonolopo, Kecamatan Mijen, Kota Semarang merupakan start-up bisnis yang memanfaatkan peluang dalam budidaya maggot yang sudah berdiri kurang lebih satu tahun. Dalam proses budidaya maggot terdapat proses penetasan telur lalat Black Soldier Fly (BSF) yang memerlukan suhu 28oC-36oC dan kelembaban sebesar 60%-80%. Apabila suhu dan kelembaban tidak stabil maka dapat mempengaruhi lama waktu proses penetasan telur. Proses penetasan telur lalat BSF membutuhkan waktu selama 3 hari. Namun, di UMKM REPRO Maggot proses penetasan telur BSF memerlukan waktu 7-8 hari. Oleh karena itu, diperlukan suatu rancangan alat penetas telur lalat Black Soldier Fly (BSF) yang dilengkapi controlling pada suhu dan kelembaban untuk meningkatkan tingkat efektivitas dan efisiensi. Perancangan ini menggunakan pendekatan metode rasional yang berisi beberapa tahap diantaranya: 1) clarifying objectives, (2) establish function, (3) setting requirement, (4) determining characteristic, (5) generating alternatives, (6) evaluating alternatives, dan (7) product improvements. Hasil uji coba yang telah dilakukan didapatkan peningkatan efisiesnsi output sebesar 86% dan efektivitas waktu 100% pada uji coba pertama, sedangkan pada uji coba kedua didapatkan efisiensi 90% dan efektivitas 33,33%.